Nexans Tracking System. An indoor positioning system using Bluetooth Low Energy - Holm, Ragnhild Kosmo (UiT Norges arktiske universitet, 2015)
Nexans Rognan is a cable manufacturer located in Nordland County. Each new cable order have a set of requirements provided by the customer. The cable specifications change in terms of characteristics of fibre optical elements, type and quality of cable armouring and dimension and amounts of electrical conductors. Due to the variety in different cables produced, they also need a wide array of different cable drums available at the plant. The drums are stored in sporadic locations around the plant and the lack of organization of the cable drums creates extra work for production workers. They estimate an yearly cost of 2-3 FTE’s is lost searching for drums. This have created a need for an indoor tracking system. The main objective of this thesis is implementing a system which should follow a cable drum from when it enters the factory for the first time, and until it is disposed or shipped out to the customer. It uses Bluetooth Low Energy (BLE), NFC, Android devices and Microsoft Azure for creating fully functional system for cable drum organization. The system heavily emphasize the use of user roles to personalize the web page for each user for creating a more seamless work flow. The system consist of different modules, performing different tasks. Three different mobile applications, a web site, a middleware and a SQL database have been created. Two of the mobile applications provides functionality for tracking the cable drums inside the factory hall. The NFC application provides functionality for identifying the drum, and for updating the information about it. The middleware does most of the work within the system. It decides whether or not the drum has moved, checks user privileges and implements methods for adding, updating and deleting from the database. The web site provides a simple user interface, and creates simple methods for a user to update the backend with correct information. The system have been designed and implemented from requirements set by Nexans Rognan. Multiple smaller, fault prone and ...